2014
DOI: 10.1007/s13762-013-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus removal from aqueous solutions containing low concentration of phosphate using pyrite calcinate sorbent

Abstract: Natural pyrite was modified by calcination under nitrogen (N 2 ) atmosphere to produce a novel sorbent for removing phosphorus (P) with low concentration from aqueous solutions. The crystallinity, porous texture, magnetic susceptibility and performance in P removal of pyrite calcinates depended on calcination temperatures. The sorbent obtained at calcination temperature of 500-600°C possessed the most efficient P removal. Solution pH in the range of 3.0-9.0 and anions of chloridion (Cl -), nitrate (NO 3 )-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Divya et al [63] stated that the presence of anions like Cl2, SO4 2-, NO 3and CO3 2did not show any significant influence on phosphate adsorption, whilst some cations such as Ca 2+ , Mg 2+ , Cu 2+ , Fe 2+ and Zn 2+ facilitate the process. These findings coincide with those reported by Chen et al [64]. They concluded that anions of Cl -, NO 3-, and SO4 2had a negligible effect on phosphorus adsorption by natural pyrite however mahatheva kalaruban et al [65] illustrates that nitrate removal efficiency using amine grafted corncob drastically fell in the presence of phosphate and chloride ions.…”
Section: Factors Affecting Adsorption Of Nutrientssupporting
confidence: 89%
“…Divya et al [63] stated that the presence of anions like Cl2, SO4 2-, NO 3and CO3 2did not show any significant influence on phosphate adsorption, whilst some cations such as Ca 2+ , Mg 2+ , Cu 2+ , Fe 2+ and Zn 2+ facilitate the process. These findings coincide with those reported by Chen et al [64]. They concluded that anions of Cl -, NO 3-, and SO4 2had a negligible effect on phosphorus adsorption by natural pyrite however mahatheva kalaruban et al [65] illustrates that nitrate removal efficiency using amine grafted corncob drastically fell in the presence of phosphate and chloride ions.…”
Section: Factors Affecting Adsorption Of Nutrientssupporting
confidence: 89%
“…The second region (493-531 • C) is associated with the process of ferrous sulfate decomposed to hematite and sulfur dioxide gas [23]. The third region (531-697 • C) and the endothermic peak at 676 • C corresponds to the process that the pyrite transformed to pyrrhotite by desulfuring as follows in Equation (3) [18]. Lastly, the fourth region (under 800 • C) is assigned to the conversion of monoclinic pyrrhotite to hexagonal pyrrhotite [24].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Therefore, in order to gain highly reactive products, our group developed a cost-effective method by thermally activating pyrite [15]. Thermally activated pyrrhotite as a promising adsorbent has been studied for the removal of various contaminants, such as Cu(II) [16], Pb(II) [17,18], U(VI) [19], and Hg 0 [20]. They all exhibit excellent adsorption characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of pyritic fill may be predominantly mudstone or sandstone, depending on the location in which it is quarried, so its adsorption capacity is potentially variable. However, mineral pyrite has been recognised as an adsorbent, particularly regarding P, and adsorption capacities of up to 1.6 mg PO 4 3− -P g −1 have been measured (Chen et al, 2015). It is known that P binding occurs in the presence of Ca, Al and Fe oxides (Egemose et al, 2012), which explains the results of the pyritic fill adsorption studies.…”
Section: Adsorption Isothermsmentioning
confidence: 99%